Myeloid Dysregulation in a Human Induced Pluripotent Stem Cell Model of PTPN11-Associated Juvenile Myelomonocytic Leukemia - Sonia Mulero-Navarro (Cell Reports, 2015)
Somatic PTPN11 mutations cause juvenile myelomonocytic leukemia (JMML). Germline PTPN11 defects cause Noonan syndrome (NS), and specific inherited mutations cause NS/JMML. Here, we report that hematopoietic cells differentiated from human induced pluripotent stem cells (hiPSCs) harboring NS/JMML-causing PTPN11 mutations recapitulated JMML features. hiPSC-derived NS/JMML myeloid cells exhibited increased signaling through STAT5 and upregulation of miR-223 and miR-15a. Similarly, miR-223 and miR-15a were upregulated in 11/19 JMML bone marrow mononuclear cells harboring PTPN11 mutations, but not those without PTPN11 defects. Reducing miR-223’s function in NS/JMML hiPSCs normalized myelogenesis. MicroRNA target gene expression levels were reduced in hiPSC-derived myeloid cells as well as in JMML cells with PTPN11 mutations. Thus, studying an inherited human cancer syndrome with hiPSCs illuminated early oncogenesis prior to the accumulation of secondary genomic alterations, enabling us to discover microRNA dysregulation, establishing a genotype-phenotype association for JMML and providing therapeutic targets.